2017
DOI: 10.18203/2349-3933.ijam20173228
|View full text |Cite
|
Sign up to set email alerts
|

Study of prevalence and pattern of peripheral neuropathy in patients with liver cirrhosis

Abstract: Background: Peripheral neuropathy is not an uncommon complication of liver cirrhosis but it is not given much clinical relevance. The pattern and prevalence of peripheral neuropathy has also not been studied extensively. Alcohol use, coexisting diseases and nutritional deficiency have been postulated as factors responsible for neuropathy. The aim of this study was to define the pattern and prevalence of neuropathy in cirrhosis and to determine any etiologic correlation.Methods: 85 patients of cirrhosis of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…Most previous studies showed a mixed pattern of peripheral nerve involvement (axonal and demyelinating, sensorimotor affection) in agreement with our findings [4,6,14]; however, other studies showed histopathologic evidence of segmental demyelination and remyelination in sural nerves of patients with hepatic neuropathy [15,16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most previous studies showed a mixed pattern of peripheral nerve involvement (axonal and demyelinating, sensorimotor affection) in agreement with our findings [4,6,14]; however, other studies showed histopathologic evidence of segmental demyelination and remyelination in sural nerves of patients with hepatic neuropathy [15,16].…”
Section: Discussionsupporting
confidence: 92%
“…If we moved to the relation between severity of liver cirrhosis and HN, previous studies showed contradictory results. While our finding of a positive interrelation accords with some studies [14,23,24], others showed no significant correlation [4][5][6].…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of peripheral neuropathy was 72.3% and was affected mainly by the duration and severity of liver cirrhosis that was determined by Child‐Pugh classification 7 . Close percentages were also found: 67.39%, 5 and 73%, 8 of cirrhotic patients despite different aetiologies of liver cirrhosis.…”
Section: Introductionmentioning
confidence: 77%
“…Nervous dysfunction could be due to the association with abnormality of glucose metabolism and hence higher prevalence of diabetes mellitus among cirrhotic patients that may reach about 20–60% of patients 5 . Also, the evidence introduced by the nerve excitability studies in the cirrhotic patients suggests depolarization probably caused by ischaemia resulting from imbalance of potent vasoconstrictors (such as endothelin) and vasodilators (such as nitric oxide) resulting in poor nerve perfusion 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation